Economic Downturn and Financing Innovative Startup Companies. (30th September 2013) - Paik, Yongwook; Woo, Heejin; Klein, Peter; Siegel, Donald; Wilson, Nick; Wright, Mike
<x xml:space="preserve">Abstract</x> This study examines how fluctuations in the amount of capital flowing into venture funds affect the financing of innovative startup companies and how economic downturns affect such financing. We argue that the nature of the economic downturn can cause differential effects on the investment pattern. We find that venture capital firms invest more in early‐stage companies than in later‐stage companies when the amount of capital flowing into the market increases. We also find that venture capital firms invest less in early‐stage companies than in later‐stage companies during an economic downturn associated with the real sector, and that they invest more in early‐stage companies than in later‐stage companies during an economic downturn associated with the financial sector. This study contributes to the entrepreneurship literature by demonstrating how macroeconomic factors affect venture capital investment decisions. The study also delineates the implications of seeking market entry via venture capital financing by entrepreneurial companies. Copyright © 2013 John Wiley & Sons, Ltd.